2015
DOI: 10.4103/0970-9290.172081
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and antifungal efficacy of Spilanthes acmella as an intracanal medicament in comparison to calcium hydroxide: An in vitro study

Abstract: SPA possesses remarkable antibacterial and antifungal activity against common root canal pathogens which are responsible for repeated endodontic failures such as E. faecalis and C. albicans when compared with medicaments like Ca(OH)2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…When diluted in 20% Tween 80, the MBC of N. sativa oil was in the range of 1.25-5% for four bacterial strains, whereas for three other bacterial strains it was 10%. For nine (Sathyaprasad, Jose, & Chandra, 2015). Our data confirm that…”
Section: Mic and Mbc/mfcsupporting
confidence: 89%
See 1 more Smart Citation
“…When diluted in 20% Tween 80, the MBC of N. sativa oil was in the range of 1.25-5% for four bacterial strains, whereas for three other bacterial strains it was 10%. For nine (Sathyaprasad, Jose, & Chandra, 2015). Our data confirm that…”
Section: Mic and Mbc/mfcsupporting
confidence: 89%
“…Its pharmacological actions within the oral cavity include local anesthetic, antibacterial, antifungal, anti‐inflammatory, and antinociceptive effects (Dubey, Maity, Singh, Saraf, & Saha, ). A petrol ether extract of air‐dried Spilanthes flowerheads possessed remarkable antibacterial and antifungal activity against common root canal pathogens when compared with calcium hydroxide (Sathyaprasad, Jose, & Chandra, ). Our data confirm that Spilanthes tincture is a potent inhibitor not only of E .…”
Section: Discussionmentioning
confidence: 99%
“…to treat enterobiasis (itching of anal area caused by pinworm infection) is also reported from the studies of pinworms and other root canal pathogens like Escherichia faecalis, Staphylococcus sp., Streptococcus sp., etc. 18 The record of medicinal plants and uses in some papers showed that the usage of decoction of bark and leaves of the Helicia robusta ( Figure 7) for treating stomachache and kidney problems in different parts of Mizoram has been reported, 19,20 and the uses of its root decoction for stomach ulcer is also recorded from other studies within Mizoram. 21 Decoction of Elaeagnus caudata leaves (Figure 8), particularly taken as medicine for menstruation and gynecological problem, is widely used in all parts of Mizoram and the utilization of fresh root extract diluted with water to prevent miscarriage is also reported from North Cachar hills, Assam.…”
Section: Resultsmentioning
confidence: 99%
“…While chlorhexidine digluconate showed reduced activity against dentin initially, extended incubation, upto 24 hours, leads to loss of 99% viability of bacteria. Sodium hypochlorite also displays inhibition by dentine and is also not much preferred as a disinfecting agent 11 .…”
Section: Assessing the Eradication Of Enterococcus Faecalis By Medicaments In Presence Of Dentinmentioning
confidence: 99%
“…The long acting activity and stability of calcium hydroxide has made it one of the most widely used medicaments. For a root canal treatment, a single visit treatment is considered advantageous over multiple visits 11 . In case of multiple visit treatment, calcium hydroxide is the most preferred medicament.…”
Section: Introductionmentioning
confidence: 99%